Out of bounds? How Gawker’s outing a married man fits into the boundaries of journalism - Tandoc, Edson C., Jr. (2020)
Gawker ignited a controversy when it published an article about a married Conde Nast executive who allegedly sought the services of a gay escort. The popular blog eventually removed the article following condemnation from readers and other journalists. Guided by the frameworks of boundary work and field theory, this study analyzed 65 news articles and 2203 online comments and found that journalists and audiences problematized Gawker’s identity as a journalistic organization and evaluated the article based on traditional standards of newsworthiness, audiences asserted their role in journalism’s larger interpretive community, and that the larger interpretive community assessed the article based on the ethics of outing. Investigating the discourse generated by this critical incident is important because it identifies where journalists and readers draw the boundaries of legitimate journalism, specifies the place of ethics in boundary discourse, and informs journalistic practice about the phenomenon of outing in the news.